A Wolf in Sheep's Clothing: A Case of Dilated Cardiomyopathy Presenting with Nonspecific Digestive Symptoms: Insights into Nonocclusive Mesenteric Ischemia - Antoine Kossaify (Case Reports in Medicine)
We report on a 32-year-old male patient who presented to the emergency room for abdominal pain associated with nausea and vomiting. The patient experienced these symptoms for the last 3 months and was taken in charge on an outpatient basis. Assessment in the emergency room showed hemodynamic collapse, there were no signs of acute surgical abdomen. Emergent cardiac echogram showed severely dilated hypokinetic cardiomyopathy. The diagnosis of acute heart failure associated with nonocclusive mesenteric ischemia was retained. A review of the pertinent literature is presented.